2020
DOI: 10.37190/abb-01544-2020-02
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the adhesion properties of calcium-phosphate coating to titanium substrate with regards to the parameters of high-frequency magnetron sputtering

Abstract: Purpose: The main goal of the work was to find the interconnection between the high-frequency magnetron sputtering parameters and the adhesion properties of CaP coatings formed on the surface of titanium substrate. Methods: Calcium-phosphate coatings, similar in composition to hydroxyapatite, were generated by high-frequency magnetron sputtering on titanium substrate at different values of high-frequency specific power over times of one and two hours. Afterwards, the generated coatings were studied using the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…As can be seen from the friction results without lubrication, the TiAlCN-2 coating has the lowest and most stable CoF compared to the other coatings, indicating that this coating has low friction resistance [ [29][30][31][32]]. In addition, low CoF can be associated with the formation of debris in the wear track, which leads to the subsequent formation of a lubricating transition layer, mainly due to an increase in carbon sp 2 [33].…”
Section: Research Discussionmentioning
confidence: 99%
“…As can be seen from the friction results without lubrication, the TiAlCN-2 coating has the lowest and most stable CoF compared to the other coatings, indicating that this coating has low friction resistance [ [29][30][31][32]]. In addition, low CoF can be associated with the formation of debris in the wear track, which leads to the subsequent formation of a lubricating transition layer, mainly due to an increase in carbon sp 2 [33].…”
Section: Research Discussionmentioning
confidence: 99%
“…Under the load of 20 N, the friction coefficient grows rapidly in the early stage, and the friction coefficient curve is smooth and keeps stable at about 0.45 at 200 s. The friction coefficient grows faster in the late stage of wear, mainly due to the serious wear of the coating. When the load is 12 N, the friction coefficient curve is relatively smooth, with values fluctuating around 0.4, and the friction coefficient starts to grow rapidly after 350 s. Comparing the friction coefficient curves under both loads, it can be found that the friction coefficient of the coating under both loads did not show a jump increase, which is mainly due to the excellent bonding strength of the coating [22]. In addition, the coating exhibited better friction performance at low loads, as evidenced by lower and smoother friction coefficient values.…”
Section: Tribological Testmentioning
confidence: 93%
“…An increase in CoF after 20 m of track length for the TiCrCN-2 coating confirms the beginning of the coating degradation process, but without serious damage to the coating. The rest of the coatings show low CoF, which indicates a high cohesive and adhesive strength of the coatings formed by the MS method [36].…”
Section: Tribological Testing Of Coatingsmentioning
confidence: 99%
“…An increase in CoF after 20 m of track length for the TiCrCN-2 coating confirms the beginning of the coating degradation process, but without serious damage to the coating. The rest of the coatings show low CoF, which indicates a high cohesive and adhesive strength of the coatings formed by the MS method [36]. To compare the results, the wear test of the coatings was carried out un conditions in the ball-on-disk system using a Si3N4 counterbody (normal lo length 100 m, track radius 7 mm).…”
Section: Tribological Testing Of Coatingsmentioning
confidence: 99%